2020
DOI: 10.3758/s13428-020-01456-7
|View full text |Cite
|
Sign up to set email alerts
|

Automatic extraction of subordinate clauses and its application in second language acquisition research

Abstract: Clause subordination is an important linguistic phenomenon that is relevant to research in psycholinguistics, cognitive and behavioral sciences, language acquisition, and computational information retrieval. The paper presents a comprehensive tool called AutoSubClause, which is specifically designed for extracting subordinate clause (SC) information from natural English production. Using dependency parsing, AutoSubClause is able to extract not only information characterizing the three main types of SCs-complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Finally, note that past studies on the EFCAMDAT found L1 transfer effects on various other linguistic structures and phenomena, including clause subordination [ 46 ], relative clauses [ 47 ], clause-initial prepositional phrases [ 48 ], grammatical morphemes [ 49 ], articles [ 50 ], and capitalization [ 44 ]. X. Jiang et al even found evidence of lexical transfer on the usage rates of certain punctuation marks (e.g., dashes) and phrases (e.g., “to my mind”) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, note that past studies on the EFCAMDAT found L1 transfer effects on various other linguistic structures and phenomena, including clause subordination [ 46 ], relative clauses [ 47 ], clause-initial prepositional phrases [ 48 ], grammatical morphemes [ 49 ], articles [ 50 ], and capitalization [ 44 ]. X. Jiang et al even found evidence of lexical transfer on the usage rates of certain punctuation marks (e.g., dashes) and phrases (e.g., “to my mind”) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the decreasing tendencies in dependency distance of these three types is that they mark the subordinate clauses. A subordinate clause is embedded within a main clause and functions as a constituent of it (Cristofaro, 2003;Chen et al, 2021). Such a structure has been found to be one of the most important types of grammatical complexity and incur higher cognitive demand on language users (Carter and McCarthy, 2006;Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A subordinate clause is embedded within a main clause and functions as a constituent of it (Cristofaro, 2003;Chen et al, 2021). Such a structure has been found to be one of the most important types of grammatical complexity and incur higher cognitive demand on language users (Carter and McCarthy, 2006;Chen et al, 2021). As a result, language users may be more pressurized and motivated to simplify such structures in order to reduce the higher processing cost resulted from it.…”
Section: Discussionmentioning
confidence: 99%
“…Extracting semantic information from unstructured text is crucial to understanding the components of a sentence. Chen et al extracted the complements, adverbials, and relational information of the essential component clause, as well as the semantic and internal structure relations of the sentence through dependent syntactic analysis, and proved through experiments that the subordinate relation of the clause is a multi-component structure rather than a single-component structure [7]. Dong et al used algebraic features and techniques to bridge the semantic gap by analyzing the semantic information of mathematical words, so as to provide a clear and complete solution to automatic mathematical problems.…”
Section: Related Workmentioning
confidence: 99%